Similarly Torn, Differentially Shorn? The Experience and Management of Conflict between Multiple Roles, Relationships, and Social Categories - Jones, Janelle M.; Hynie, Michaela (Frontiers in Psychology, 2017)
In three studies we examined the experience and management of conflict between different types of multiple identities. Participants described a conflict between pairs of role, relational, or social identities before rating the experience (i.e., magnitude, stress, growth) and management of conflict on a newly developed scale assessing four strategies: reconciliation, where identities are integrated, realignment, where one identity is chosen over another, retreat, where both identities are avoided, and reflection, where fit (with others, situation) determines identity selection. In general, the types of identities mattered for conflict management but not its experience: Magnitude and growth did not differ, however stress was greater for role identity conflicts (Study 3 only) and participants endorsed the use of more realignment for role conflicts (Study 2) and more retreat for relational conflicts (Study 3) relative to other types of identity conflicts. Furthermore, findings suggested that the perceived flexibility of identities, not their importance or valence, were associated with realignment and retreat for roles and with retreat for relationships. Experiencing conflicts between multiple identities leaves people similarly torn, but multiple roles and relationships may be differentially shorn to manage conflict.